2012
DOI: 10.1002/mus.23505
|View full text |Cite
|
Sign up to set email alerts
|

Increased nerve vascularization detected by color doppler sonography in patients with ulnar neuropathy at the elbow indicates axonal damage

Abstract: IVUS in the ulnar nerve can be detected in patients with UNE and is associated with nerve enlargement and clinical and electrodiagnostic severity. In addition, IVUS is associated with axonal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 18 publications
0
57
1
1
Order By: Relevance
“…A common finding is the presence of detectable intraneural blood flow (INBF), which often correlates with nerve size and electrophysiological severity. Detectable INBF has also been shown to be associated with axonal loss . Of interest, none of these studies reported the detection of INBF in healthy subjects, suggesting that the presence of nerve hypervascularity may be pathological.…”
mentioning
confidence: 99%
“…A common finding is the presence of detectable intraneural blood flow (INBF), which often correlates with nerve size and electrophysiological severity. Detectable INBF has also been shown to be associated with axonal loss . Of interest, none of these studies reported the detection of INBF in healthy subjects, suggesting that the presence of nerve hypervascularity may be pathological.…”
mentioning
confidence: 99%
“…Intraneural hypervascularization in penetrating nerve injury seems to be a more robust and consistent phenomenon in comparison to other peripheral nerve conditions, such as entrapment neuropathies or inflammatory neuropathies, resembling the intensity and extension seen in peripheral nerve sheath tumors, such as schwannomas . A direct comparison is, however, hampered by methodological issues, as either no quantification of flow signals was performed, or a different method was used in these studies.…”
Section: Discussionmentioning
confidence: 88%
“…Presently, the demonstration of any intraneural blood flow is usually considered to be hypervascularization of the nerve and a pathological sign in conditions such as carpal tunnel syndrome, ulnar neuropathy at the elbow, chronic inflammatory demyelinating polyneuropathy, leprosy, and certain peripheral nerve sheath tumors . However, no ultrasonographic data are available concerning vascularity and nerve regeneration following nerve trauma, where the development of vasculature has been shown to be a crucial element in animal models .…”
mentioning
confidence: 99%
“…Assessment of intraneural vascular flow is based on Doppler and power Doppler techniques (the latter being particularly effective to show small vessel flow), which enable depiction of the nerve circulatory system 26 . In healthy nerves, vascularization cannot be detected, whereas increased intraneural vascularization can be seen in entrapment 27 , inflammatory neuro pathies 22 and neurolymphomatosis 28 . The clinical value of intraneural vascular flow is currently under debate.…”
Section: Ultrasonographymentioning
confidence: 99%